PENGARUH BUDAYA ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI (STUDI KASUS PADA BADAN KEUANGAN DAN ASET DAERAH KABUPATEN SLEMAN) - Andira Ramadha Arundita; Didik Subiyanto; Ignatius Soni Kurniawan (Jurnal Fokus Manajemen Bisnis, 2021)
The purpose of this study was conducted to determine the effect of the relationship between organizational culture and organizational citizenship behavior (OCB) with organizational commitment as a mediating variable. This research was conducted in the Regional Financial Institutions and Assets of Sleman Regency. The sample in this study were all employees of the Regional Financial Institutions and Assets of Sleman Regency. Data collection by distributing questionnaires using a Likert scale to measure indicators. The technique used in this research is descriptive analysis. The results of this study indicate that organizational culture has a positive and significant effect on organizational commitment, organizational culture has a positive and significant effect on organizational citizenship behavior (OCB), organizational commitment has a positive and significant effect on organizational citizenship behavior (OCB) and organizational commitment acts as mediation affect organizational culture and organizational citizenship behavior (OCB).